LEARNING THROUGH MOBILE: EXPLORING THE VIEWS OF POLYTECHNIC ESL LEARNERS - Harwati Hashim; Melor Md. Yunus; Mohamed Amin Embi (Siliwangi University, 2018)
The purpose of this paper is to explore how polytechnic English as Second Language Learning (ESL) learners perceived the use of mobile technology in supporting and enhancing their learning. Students from four selected polytechnics were requested to respond to two open-ended questions regarding the advantages and challenges of using mobile technology in learning ESL. A total of 194 students responded to the questions. The responses provided by the students showed that they agreed mobile technology could be a potential tool to support and enhance their learning. Nevertheless, majority of them stated concerns about not having internet access or connection, inaccurate information and high level of English used on the internet. This implies that in order for mobile technology to be employed or fully utilised for English as Second Language (ESL) learning, it is important for polytechnic institutions to overcome the challenges to ensure the affordances of mobile technology could be fully optimised, including the consideration of the pedagogical implications in ESL context.